A review of doped lanthanum gallates as electrolytes for intermediate temperature solid oxides fuel cells: From materials processing to electrical and thermo-mechanical properties. Issue 1 (January 2016) - Morales, M.; Roa, J.J.; Tartaj, J.; Segarra, M.
Abstract The present review is focused on SrO- and MgO-doped lanthanum gallates (LSGMs), specifically in those key aspects related to their implementation as electrolyte for Intermediate Temperature Solid Oxide Fuel Cells. After a brief survey of the state-of-the-art for the LSGMs, the attention is focused on the ionic transport properties for the relevant compositions. The design, manufacturing and performance of cells using LSGM as electrolyte are discussed along the review. Particular interest is given to the impact of synthesis routes for lowering their sintering temperatures. A short discussion on the chemical compatibility between electrolyte and electrodes in cells is also included. Afterwards, mechanical and thermal properties of LSGMs reported determined though conventional methods at different working temperatures are discussed. Finally, the microstructural and compositional effects related to their electrical and mechanical properties at micro- and nanometric length scale are assessed as a complementary tool for future developments in solid electrolyte materials.